ANALISIS YURIDIS DALAM PENERAPAN EFEKTIVITAS PELAYANAN PUBLIK: (Studi Kasus SP4N LAPOR Kabupaten Demak) - Rian Sacipto; Hetiyasari Hetiyasari (Program Studi Administrasi Publik, FISIP, Universitas Tulang Bawang Lampung, 2023)
This research was structured to find out and analyze the effectiveness of public services in Demak district, especially in the Demak district government's reporting channel. Along with technological developments, the Demak Regency Communication and Informatics Service (DINKOMINFO) is moving to provide efforts and innovation on issues regarding public services. The program provided is in the form of public services in the form of reports through booths, websites, SMS, social media, and applications to convey public complaints. This research is a qualitative descriptive study with a process of document analysis and observation. The information taken comes from a sample involving the people of Demak district. At this stage of the study, an analysis of public knowledge and the effectiveness of the number of users of the complaint report service was used, namely Hallo Demak and the SP4N report application, Demak district. The results of the study obtained the effectiveness of public services in Demak district through SP4N reports that the Demak district had experienced an increase in the range from December 2020 to mid-January 2021 in a period of 1.5 months receiving a total of 212 complaints, but the data was not optimal and uneven. There are still many people who do not know and even use the service. The lack of equality in the form of direct introduction and involving many parties such as students, university students, laborers, village officials, has an effect on ordinary people to participate and feel the benefits of the facilities provided. Keywords: SPAN; Report; Introduction; Benefits.